Avaliação do uso de bambu como estrutura em alvenaria de blocos de solo-cimento - Guimarães, Ricardo José (2017)
The use of materials that involve less energy in the production process, are more easily absorbed by nature and generate less pollutants and waste is of great interest for the future of the planet and its inhabitants. This paper presents themes of sustainability for civil construction, such as the potentialities and technical feasibility of an emerging material in Brazil, bamboo, which fits perfectly in the question, since it is an element that has good engineering properties and with great availability in rural areas. In addition to this, soil-cement blocks, so well used in today's buildings, also intended for sustainable buildings, are part of the research. In an experiment that sought to unite the academic teaching with practice, a prototype of wall in blocks of soil-cement structured with bamboo sticks was developed. The main elements of the research were the evaluation of the strengths of the compression-conditioned soilcement blocks, of bamboo to axial compression and bending, and of the combination of soil-cement / bamboo blocks. Results of 153 kN were obtained for the walls and 7.45 MPa for the soil cement blocks in the compression tests. In the bamboo compression tests, the obtained values resulted in 119.09 MPa and 96.21 MPa for test bodies with and without nodes, respectively. The results obtained in the tests developed with the materials separately and also from the set showed that both perfectly fit the one proposed in this work, which allows to consider adequate the methodology used in the preparation of the test bodies as well as in the execution of the related tests.